Open Access in Theory and Practice The Theory-Practice Relationship and Openness - Pinfield, Stephen (Taylor & Francis, 2020)
"Open Access in Theory and Practice investigates the theory-practice relationship in the domain of open access publication and dissemination of research outputs. Drawing on detailed analysis of the literature and current practice in OA, as well as data collected in detailed interviews with practitioners, policymakers, and researchers, the book discusses what constitutes "theory", and how the role of theory is perceived by both theorists and practitioners. Exploring the ways theory and practice have interacted in the development of OA, the authors discuss what this reveals about the nature of the OA phenomenon itself and the theory-practice relationship. Open Access in Theory and Practice contributes to a better understanding of OA and, as such, should be of great interest to academics, researchers, and students working in the fields of information science, publishing studies, science communication, higher education policy, business, and economics. The book also makes an important contribution to the debate of the relationship between theory and practice in information science, and more widely across different fields of the social sciences and humanities."